2019
DOI: 10.1242/jcs.231514
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity within collective invasion packs drives leader and follower cell phenotypes

Abstract: Collective invasion, the coordinated movement of cohesive packs of cells, has become recognized as a major mode of metastasis for solid tumors. These packs are phenotypically heterogeneous and include specialized cells that lead the invasive pack and others that follow behind. To better understand how these unique cell types cooperate to facilitate collective invasion, we analyzed transcriptomic sequence variation between leader and follower populations isolated from the H1299 non-small cell lung cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 100 publications
0
46
0
Order By: Relevance
“…We next performed RNA-seq on isolated leader and follower cells and the parental population to assess gene expression differences (13). Principal component analysis showed that parental, leader, and follower cells each had distinct gene expression patterns ( fig.…”
Section: Epigenetic Heterogeneity Between Lung Cancer Leader Cells Anmentioning
confidence: 99%
See 2 more Smart Citations
“…We next performed RNA-seq on isolated leader and follower cells and the parental population to assess gene expression differences (13). Principal component analysis showed that parental, leader, and follower cells each had distinct gene expression patterns ( fig.…”
Section: Epigenetic Heterogeneity Between Lung Cancer Leader Cells Anmentioning
confidence: 99%
“…RNA-seq was performed in triplicate on H1299 parental, leader, and follower cells. RNA library preparation and sequencing were performed by the Emory Integrated Genomics Core and Omega BioTek Inc., as previously described (13). Data processing, read alignment, quality control, and statistical analyses were performed by the Emory Biostatistics and Bioinformatics Shared Resource, as previously described (13).…”
Section: Rna-seq and Gseamentioning
confidence: 99%
See 1 more Smart Citation
“…Because leader cells are crucial for collective invasion in 3‐dimensional assays, 11 we hypothesized that patients with NSCLC with genetic evidence of leader cells within the primary tumor could be at higher risk for disease progression and recurrence. Our previous data showed that H1299 leader and follower cells contain distinct mutational profiles 16 . Additional inclusion of known variants from the dbSNP database 23 resulted in 17 leader‐specific mutations and 18 follower‐specific mutations (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, point mutations could affect protein function without affecting gene expression. For example, we previously showed that a leader‐specific mutation in ARP3, while not affecting messenger RNA expression in leader cells, conferred leader cell behavior when it was introduced into follower cells 16 …”
Section: Discussionmentioning
confidence: 99%